A study to assess the effectiveness and perception of students regarding Case Based Learning over traditional teaching method in Community Medicine - Annadani, Rachana R; Undi, Malatesh (Indian Journal of Community Health, 2021)
Background: Case based learning (CBL) among medical undergraduates, has more interactive sessions and students been involved in thinking, analyzing and interpretation. However, it is not clear if it is reflected in their assessment results. Aim & Objective: To assess the effectiveness and perception of Case Based Learning over the traditional TL method used in Community Medicine among second year medical undergraduates. Settings and Design: A randomized controlled study was conducted among second year medical undergraduates studying in a government medical college in coastal Karnataka. Methods and Material: 143 Students were randomly allocated into two groups- Group A underwent traditional teaching and Group B underwent Case Based learning. The effectiveness of TL methods was assessed using Multiple Choice Questions (MCQs). Group B’s perception regarding CBL was also obtained. Statistical analysis: Inter-group and intra-group mean scores of the pre-test, post-test and retention tests of MCQs of the students were compared using independent t-test and paired t-test respectively. Results: Statistically significant difference was observed in post-test and retention test scores between the groups. Students perceived CBL aroused interest and encouraged self-directed learning. Conclusion: CBL was effective over the traditional teaching learning method.